Development of a logarithmic module equipped with a jigsaw cooperative model - Jitu Halomoan Lumbantoruan; Evi Deliviana (Jurnal Elemen, 2023)
The teacher's task is to compile lesson plans, books, or modules assess and evaluate. However, the fact is that the low learning outcomes are due to the difficulty level of the book. The results of the 2022 study show that students' scores are below 75, which is 74.80. Urgency, there is a difference between teacher assignments, expectations, and learning outcomes. The research aims to design practical and effective modules. The research method used is Research and Development (R&D): Determination, Design, Development, Implementation, and Evaluation. The subject is high school, and the subject is 32 students. They are collecting data with assessment instruments from material experts, teachers, and students. Modules are measured by practicality through instruments, and tests measure effectiveness. Analysis technique with validation. Average values and interpretations. As a result, the logarithmic module is practical, effective, and can increase value. The validation of material experts and math teachers assessed 92.35% and 91.45% in the very good category. Student assessment of the module is 95.81%, a very good category. Post-test learning outcomes use the 90.28 module, and those that do not use the 68.40 module.